Effect of marriage upon academic achievement - Hotchkiss, Courtlyn, author; Comstock, George A., advisor; Novak, Benjamin J., committee member; Heilig, Herb, committee member; Davis, Robert W., committee member; Guard, Harris T., committee member; Stinson, Dean, committee member (Colorado State University. Libraries, 1948)
To view the abstract, please see the full text of the document.
Keywords: Married students; Veterans -- Education (Higher); College students